The physics and Metaphysics of the sensitivity of calorimetric instruments and human senses. Issue 3 (21st March 2017) - Das, Dilip K.
Abstract : The onset temperature for a reaction detected by an apparatus in an experimental study is an overestimated value compared with the actual value existing within large batches. Models are used to estimate the "actual value" for large batches. The onset temperature is dependent on the Phi‐factor (thermal inertia), adiabaticity, and detection sensitivity of the calorimeter. It is therefore advisable to penalize the detected onset temperature by an arbitrary number, such as 50°C for Accelerating Rate Calorimeter (ARC), to arrive at the recommended (Adjusted) onset decomposition or reaction temperature for the purpose of setting control parameters in operations. The influence of Phi‐factor and detection‐ sensitivity of the Heat‐Wait‐Search mode in the ARC on the detected onset temperature is discussed. A parallel is drawn between the instrumental sensitivity1 in the phenomenal world and the mental sensitivity in the noumenal world. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 280–283, 2017